The Mythopoetic Space of Baltic Cities in the Selected Short Stories by Max Frei - Vorontsova, Kristina (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2024)
This article attempts to analyze the mythopoetic space of the capitals of the Baltic states in selected stories by Russian-speaking fantasy author Svetlana Martynchik (born in Odesa in 1965, pseudonym – Max Frei), published during a time of global upheaval for European culture, namely after 2022. The Lithuanian capital, especially in comparison with Riga and Tallinn, emerges as a liminal space where characters find it most convenient to transition between the world of wonders and everyday reality. The vivid geography of Vilnius includes real topography imbued with stereotypical connotations, as well as established loci tied to urban practices (courtyard, avenue, supermarket), transforming into a functional field for constructing the author’s urban myths and reproducing pre-existing cultural ones. Special attention is given to a group of Scandinavian myths in the context of the coronavirus pandemic, which the author perceives as yet another, and this time ultimate, decline of Europe and civilization as a whole. Mythopoetic Vilnius, forming a unified northern cultural space together with Riga and Tallinn, becomes a realm of escapism, acquiring features of Eden and an anti-Babylon.